Efektivitas Model Two Stay Two Stray (TSTS) dan Jigsaw Terhadap Karakter Tanggung Jawab Siswa Kelas V Pembelajaran PPKn - Ria Setianingrum; Agustina Tyas Asri Hardini (STKIP Andi Matappa Pangkep, 2023)
Learning in the world of education is expected to have a balance not only emphasizing the cognitive domain and psychomorphic skills but balanced with a positive personality so that students wisely use all their abilities including the values of responsibility. This study aims to determine the effectiveness of the Two Stay Two Stray and Jigsaw cooperative learning models in improving the responsible character of fifth grade students. This type of research is the Quasi Experiment with Pretest-Posttest Control Group Design. The research location was at Gugus Merbabu Elementary School, Semarang Regency. The difference in the average value of the experimental group was 37.47 higher than the control. The frequency of 9% is that the category is visible, 13% is starting to develop and 78% is already entrenched. The results of the research conducted t-test there is a difference from the results of t-count (2-tailed) with a sig value of 0.0045. This means that H0 is rejected and Ha is accepted. Strengthened by the results of the data-test, it can be concluded that the character of responsibility of fifth grade elementary school students using the Two Stay Two Stray learning model is significantly higher than the jigsaw model.